Management of adrenal insufficiency: A survey of perceptions and practices of physicians from the Middle East and North Africa - Beshyah, Salem; Ali, Khawla (Journal of Diabetes and Endocrine Practice, 2021)
Introduction: Treatment of adrenal insufficiency (AI) requires correct lifelong use of glucocorticoids (GCs) with early dose adjustments to cover the increased demand in stress to avoid life-threatening emergencies. Objectives: We determine the current specific knowledge of physicians in a convenience sample on the pathophysiological and clinical aspects of AI in the two regions of North Africa and the Middle East. Materials and Methods: Participants (n = 96) were invited to complete an electronic questionnaire with various possible answers on the subject of multiple-choice questions covering physiology, pharmacology, and clinical management and define respondents' professional profiles. Results: The present study suggests that in the investigated settings, physicians' knowledge of physiology and pharmacology GCs, medical replacement strategies in AI, and prevention of adrenal crisis may be insufficient. Great knowledge gaps were demonstrated. Conclusions: There is a need for continuous structured education and training on AI in both general medical and endocrine forums.
Keywords: Adrenal crisis; adrenal insufficiency; glucocorticoid replacement therapy; hydrocortisone; prednisolone